Lessons from the economics of crime What reduces offending ? - Mastrobuoni, G.; Cook, P. J. & Others; Machin, S.; Cook, P. J. & Others (Cambridge Massachusetts Institute of Technology, 2013)
1) Policy choice and normative framework